2010
DOI: 10.1007/s00251-010-0437-0
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variations in the CεmX domain of human membrane-bound IgE

Abstract: The epsilon chain of membrane-bound IgE (mIgE) is expressed predominantly as a "long" isoform, containing an extra segment of 52 amino acid (a.a.) residues, referred to as C epsilon mX, between the CH4 domain and the C-terminal membrane-anchoring transmembrane peptide. C epsilon mX results from an alternative splicing of the epsilon RNA transcript at 156-bp upstream of the splicing acceptor site used by the "short" isoform. Here, based on an analysis of the C epsilon mX genomic DNA sequences of 320 subjects re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…These include ß-thalassemia, spinal muscular atrophy and type 1 neurofibromatosis, among others (reviewed in [4] , [40] , [43] ). Transcripts encoded by several asthma-associated genes also undergo alternative splicing [20] , [31] , [34] , [36] , [37] , [39] , [44] , although only in the case of cysteinyl leukotriene type I receptor does there seem to be a connection to asthma immunopathogenesis [34] . These data, coupled with the enormous biological and pathological importance of alternative splicing, suggest that it is highly likely that alternative splicing contributes to asthma pathogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…These include ß-thalassemia, spinal muscular atrophy and type 1 neurofibromatosis, among others (reviewed in [4] , [40] , [43] ). Transcripts encoded by several asthma-associated genes also undergo alternative splicing [20] , [31] , [34] , [36] , [37] , [39] , [44] , although only in the case of cysteinyl leukotriene type I receptor does there seem to be a connection to asthma immunopathogenesis [34] . These data, coupled with the enormous biological and pathological importance of alternative splicing, suggest that it is highly likely that alternative splicing contributes to asthma pathogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…CemX is present in me but not in membrane-bound immunoglobulin of other isotypes. To date, only two allelic forms differing by a leucine or valine at position 16 along the CemX sequence (which generally does not affect antigenicity) have been found 14 . Although the threedimensional (3D) structure of CemX remains unsolved, previous work showed that two cysteines in CemX form an intrachain disulfide bond (Cys-18 with Cys-39 or Cys-41), while the other two cysteines form an interchain bridge 15 .…”
mentioning
confidence: 99%